GAMBARAN PENGETAHUAN SISWA KELAS XII SMA NEGERI 7 MANADO TERHADAP MIOPIA - Lupa, Viany S. H.; Saerang, J. S. M.; Tongku, Yamin (Universitas Sam Ratulangi, 2016)
Abstract: Nearsightedness is a refractive disorder which is the rays enter the eye without accommodation and will be refrated in the front of retina. Nearsightedness is one of the causes of low vision in children. Eye health in school student is important in learning activities. Many students do not understand the importance of knowledge towards nearsightedness. Knowledge is a very important domain that will affect an action. This was a descriptive study. This study aimed to determine the description of student grade XII knowledges at SMA Negeri 7 Manado towards nearsightedness. The results showed that the level of knowledge of student grade XII of SMA Negeri 7 Manado towards nearsightedness was still considered enough with a percentage of 56%.Keywords: knowledge, student, nearsightednessÂ Abstrak: Miopia adalah suatu kelainan refraksi dimana sinar-sinar sejajar masuk ke bola mata tanpa akomodasi akan dibiaskan di depan retina. Miopia adalah salah satu penyebab penurunan ketajaman penglihatan pada anak-anak. Penglihatan yang baik sangat penting dalam proses belajar mengajar. Banyak pelajar yang belum memahami pentingnya pengetahuan tentang miopia. Pengetahuan merupakan domain yang sangat penting untuk terbentuknya tindakan seseorang. Jenis penelitian ini deksriptif. Penelitian ini bertujuan untuk mengetahui gambaran pengetahuan siswa kelas XII SMA Negeri 7 Manado terhadap miopia. Hasil penelitian menunjukkan bahwa tingkat pengetahuan siswa kelas XII SMA Negeri 7 Manado terhahap miopia masih dianggap cukup dengan persentase sebesar 56%. Kata kunci: pengetahuan, siswa, miopia